A homogeneous lithium alloy and a preparation method and application thereof

CN122979683APending Publication Date: 2026-10-27CHANGSHA FULU NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611067961.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-03-02
Filing Date
2026-07-17
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0042]本发明的制备方法不会出现过烧和溅射现象,且制备得到的锂合金不仅成分分布均匀而且产率高,将其作为锂离子电池材料时还具有优异的电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979683A_ABST
    Figure CN122979683A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of homogeneous lithium alloy and its preparation method and application, belong to lithium negative electrode preparation technical field.The method includes: lithium metal is melted and handled to obtain molten lithium;M metal is divided into N parts, wherein N≥2, and N is integer;The molar amount of each M metal is independently not more than 5.5mol% of the molar amount of lithium metal;First M metal is first molten alloying with molten lithium to obtain first lithium-M alloy;After remelting first lithium-M alloy, second M metal is second molten alloying to obtain second lithium-M alloy;Repeat the step until after remelting N-1 lithium-M alloy, N M metal is N molten alloying to obtain homogeneous lithium alloy.The method controls the temperature, feeding mode, feeding amount and other parameters of smelting process accurately, prevents material from violent reaction, avoids material sputtering and overburning phenomenon, and improves the yield of lithium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a homogeneous lithium alloy, its preparation method and application, belonging to the field of lithium anode preparation technology. Background Technology

[0002] In recent years, the demand for energy density in energy storage and power batteries has been increasing. However, the specific capacity of traditional lithium-ion battery anode materials has reached its limit, making it difficult for lithium-ion batteries to meet these demands. The extremely high theoretical specific capacity of lithium metal anodes (3860 mAh / g) has made it possible to further develop high-energy-density batteries. Currently, lithium metal anodes have a very short lifespan due to dendrite growth and numerous side reactions caused by high activity during battery use. Furthermore, the rapid growth of lithium dendrites under high current and the drastic volume changes under high capacity can potentially trigger short circuits and lead to battery safety issues, which also poses a significant obstacle to the market application of these batteries.

[0003] Currently, lithium metal anodes suffer from short lifespans due to irregular dendrite growth during battery cycling and adverse side reactions with the electrolyte. Furthermore, the rapid growth of lithium dendrites under high current leads to battery volume expansion, increasing safety risks and hindering the further expansion and development of the lithium metal battery market.

[0004] As research progresses, alloyed anodes hold promise for solving the aforementioned challenges. Chinese patent (publication number CN115986064A) discloses a method for preparing a high-entropy lithium alloy anode. This method involves heating and melting metallic lithium with various other metals or non-metals at high temperatures to obtain a multiphase high-entropy alloy liquid composed of lithium alloy and non-lithium alloy phases. By cooling the multiphase high-entropy alloy liquid to room temperature, a micro / nanoscale three-dimensional framework network structure of the multiphase high-entropy alloy is obtained. In this structure, lithium atoms account for 20-50% of the total atomic ratio in the high-entropy lithium alloy anode material, while other metals and / or non-metals account for 1-50%. This effectively reduces local current density and suppresses lithium dendrite formation. The high-entropy alloy framework network contains inert alloy components, which helps improve the stability of the three-dimensional framework and the constancy of the anode volume, as well as enhance the lithium affinity of the three-dimensional framework, thereby improving the battery's cycle life. However, due to its complex composition, it is difficult to achieve uniform composition across all regions of the high-entropy alloy framework.

[0005] Chinese patent (publication number CN119663387A) discloses an electrodeposition method for preparing lithium alloy anodes for solid-state batteries, relating to the field of lithium alloy anode sheet preparation. The method includes the following steps: S1, firstly, a lithium sheet and a deposited metal sheet are fixed inside an electrodeposition apparatus, with the lithium sheet connected to the positive terminal of an external power supply and the deposited metal sheet connected to the negative terminal of the external power supply. This electrodeposition method for preparing lithium alloy anodes for solid-state batteries involves immersing the deposited metal sheet in a lithium-containing electrodeposition solution for electrodeposition treatment. By controlling the current density, deposition time, and electrodeposition process, the lithium content and surface morphology of the lithium alloy anode are controlled, achieving precise control over the lithium loading and the uniformity of the lithium alloy bulk phase. However, this process only optimizes the surface of the lithium metal anode, with limited effect on substrate gain. Summary of the Invention

[0006] To address the problems existing in the prior art, one of the objectives of this invention is to provide a method for preparing homogeneous lithium alloys. This method, by precisely controlling parameters such as temperature, feeding method, and feeding amount during the melting process, can prevent violent reactions of materials during melting, avoid material splashing and overheating. This method can produce lithium alloys with uniform composition distribution and also improve the yield of lithium alloys.

[0007] The second objective of this invention is to provide a homogeneous lithium alloy that does not exhibit overheating, has a high yield, and has a very uniform composition distribution.

[0008] A second objective of this invention is to provide applications of homogeneous lithium alloys as materials for lithium metal batteries. When used as a negative electrode material for lithium metal batteries, homogeneous lithium alloys exhibit excellent electrochemical performance and mechanical strength.

[0009] To achieve the above objectives, a first aspect of the present invention provides a method for preparing a homogeneous lithium alloy, the method comprising:

[0010] (1) Melt lithium metal to obtain molten lithium;

[0011] (2) Divide the metal M into N parts, where N≥2 and N is an integer; the molar amount of each part of the metal M is independently controlled within 5.5 mol% of the molar amount of lithium metal; the metal M is selected from at least one of bismuth, indium, silver, gold, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, tin, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, cadmium, antimony, hafnium, tantalum, tungsten, rhenium, iridium, platinum, mercury, thallium, lead, aluminum and polonium;

[0012] (3) The first batch of M metal is mixed with the molten lithium for the first melt alloying, and then naturally cooled to obtain the first batch of lithium-M alloy;

[0013] (3) After remelting the first lithium-M alloy, it is mixed with the second M metal for a second melt alloying and then cooled naturally to obtain the second lithium-M alloy; repeat this step until the N-1th lithium-M alloy is remelted and then melt alloyed with the Nth M metal for the Nth time, and then cooled naturally to obtain a homogeneous lithium alloy.

[0014] The conditions for the first melting alloying, the second melting alloying, ... the Nth melting alloying are each independent: temperature of 600℃~1000℃, holding time of 1~4h;

[0015] Based on the total molar amount of the M metal and the lithium metal, the total molar amount of the M metal is 5~30 mol.

[0016] Given that lithium is an alkali metal with extremely high chemical reactivity, its reaction with metal powders, especially bismuth, is accompanied by violent exothermic reactions, with instantaneous temperatures exceeding 500°C and material sputtering. To avoid excessively violent reactions and material spraying, this invention first melts elemental lithium to obtain molten lithium, then adds a specific amount of metal M for further melt alloying to obtain a pre-alloy. This pre-alloy is then remelted, and another specific amount of metal M is added, followed by melt alloying again. This cycle is repeated until a homogeneous lithium alloy is obtained. Furthermore, the inventors discovered that the melt alloying temperature must be strictly controlled; too low a temperature will cause metal segregation, while too high a temperature will lead to overheating.

[0017] This invention relates to a method for melt alloying by remelting a pre-alloyed component and adding a specific amount of M metal in stages. Through the combination of melt alloying processing conditions and other technical features, the method prevents overheating and material sputtering during the preparation of lithium alloys, while also ensuring a uniform composition distribution of the prepared lithium alloy.

[0018] As a preferred embodiment, the metal M is selected from bismuth, indium, tin, zinc, aluminum, and silver.

[0019] As a more preferred embodiment, the metal M is bismuth.

[0020] As a preferred embodiment, the purity of the M metal is ≥99wt%.

[0021] As a preferred embodiment, the purity of the lithium metal is ≥99wt%.

[0022] As a preferred option, the addition time for each part of M metal to molten lithium or remelted lithium-M alloy is 3 to 5 minutes.

[0023] As a preferred embodiment, the remelting temperature is 170℃~200℃, and the holding time is 30~90min.

[0024] As a preferred embodiment, the conditions for melting lithium metal include: a melting temperature of 180~200℃, a stirring rate of 100~200 rpm, and a holding time of 30~60 min. Under these preferred conditions, lithium metal can be completely melted into a liquid state.

[0025] As a preferred option, the heating rate of the melting process is 5~10℃ / min.

[0026] As a preferred method, the first melting alloying, the second melting alloying, and so on up to the Nth melting alloying are all carried out under stirring conditions, with each stirring rate independently set at 200-250 rpm. Too low a stirring speed will cause uneven melt flow and segregation during cooling; too high a stirring speed will easily lead to melt splashing, creating a safety hazard.

[0027] As a preferred approach, each molar amount of M metal independently accounts for 1.5 to 5.5 mol% of the molar amount of elemental lithium metal. Adding too much M metal each time will lead to uneven stirring and an overly vigorous reaction, causing the stirring temperature to rise rapidly due to the exothermic reaction and resulting in overheating; adding too little will result in low efficiency and reduced yield.

[0028] As a more preferred option, each molar amount of M metal independently accounts for 1.5 to 4.5 mol of the molar amount of lithium metal.

[0029] As a preferred embodiment, the content of the first M metal is not less than the content of the second M metal, the content of the second M metal is not less than the content of the third M metal, and the content of the (N-1)th M metal is not less than the content of the Nth M metal. The inventors have discovered that, in actual operation, a lower M metal content in a later addition compared to a previous addition results in a decrease in the yield of the lithium-bismuth alloy.

[0030] As a preferred embodiment, based on the total molar amount of the M metal and the lithium metal, the amount of the M metal is 5-20 mol%. More preferably, the amount is 5.6-20 mol%.

[0031] As a preferred option, the lithium alloy is prepared entirely in an argon atmosphere, wherein the O content in the argon atmosphere is <10ppm and the H2O content is <10ppm.

[0032] As a preferred option, both the melting process and the melt alloying are carried out in a dual planetary stirring furnace.

[0033] A second aspect of the present invention is to provide a homogeneous lithium alloy prepared by the preparation method described in the first aspect above.

[0034] A third aspect of the present invention is to provide the application of the homogeneous lithium alloy described in the second aspect above as a lithium metal battery material.

[0035] As a preferred embodiment, the homogeneous lithium alloy is rolled in an argon atmosphere using a rolling mill to obtain a lithium alloy foil, which is then used as the negative electrode material for a lithium-ion battery.

[0036] As a preferred embodiment, the speed of the roller press is 80~150 rpm. The rolling temperature is set according to the type of alloy, ranging from 25~100℃.

[0037] This invention does not have special requirements on the number of rolling processes; multiple rolling processes can be performed according to the target thickness.

[0038] As a preferred embodiment, the thickness of the lithium alloy foil is 5 to 100 micrometers.

[0039] As a preferred option, the cathode material of the lithium-ion battery is selected from at least one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, and lithium iron phosphate.

[0040] This invention does not impose any special requirements on the electrolyte for lithium-ion batteries; conventional electrolytes within the art can be used. Exemplarily, any of the following can be used: a mixed solution of 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in dioxolane (DOL) / ethylene glycol dimethyl ether (DME) and 2% LiNO3; a mixed solution of 0.2M LiPF6, 0.2M LiBF4, and 0.8M lithium difluorooxalate borate (LiDFOB) in diethyl carbonate (DEC): fluoroethylene carbonate (FEC) = 2:1 vol%; a mixed solution of 1M LiTFSI in DME:DOL = 1:1 vol%; or a mixed solution of 1M LiPF6 in ethylene carbonate (EC):DEC = 1:1 vol%.

[0041] Compared with the prior art, the present invention has at least the following advantages:

[0042] The preparation method of the present invention does not cause overheating and sputtering, and the prepared lithium alloy not only has a uniform composition distribution and high yield, but also has excellent electrochemical performance when used as a lithium-ion battery material. Attached Figure Description

[0043] Figure 1 These are optical photographs and scanning electron microscope images of the lithium bismuth alloy foil prepared in Example 1. Figure 1 Image (a) is a picture of the actual object. Figure 1Image (b) is a cross-sectional scanning electron microscope image of a lithium-bismuth alloy foil. Figure 1 Image (c) in the image is a scanning electron microscope (SEM) image of the surface of a lithium-bismuth alloy foil. Figure 1 In the figure, (d) represents the energy spectrum of bismuth element distribution on the surface of the lithium-bismuth alloy foil. Figure 1 As can be seen, the thickness of the obtained lithium-bismuth alloy foil is 98.9 μm, and the bismuth element is uniformly distributed on the surface.

[0044] Figure 2 This is the XRD characterization diagram of the lithium-bismuth alloy foil prepared in Example 1. As can be seen from the figure, the bismuth element is uniformly distributed in the lithium-bismuth alloy foil.

[0045] Figure 3 The lithium-bismuth alloy prepared in Example 1 and the pure lithium metal prepared in Comparative Example 1 were assembled into a symmetrical battery at a current density of 5 mA cm⁻¹. -2 The dough mixing capacity is 5mAh cm -2 The results of long-cycle testing under the specified conditions are shown in the figure. As can be seen from the figure, the obtained lithium-bismuth alloy anode has a cycle life exceeding 3000 hours, exhibiting high current density and areal capacity.

[0046] Figure 4 The lithium-bismuth alloy prepared in Example 1 and the pure lithium metal anode prepared in Comparative Example 1 were assembled into a symmetrical battery, and the battery performance was 0.5~4 mA cm⁻¹. -2 Cyclic test graphs at multiple current densities are shown. The graphs demonstrate that the lithium-bismuth alloy anode can cycle stably at multiple current densities, exhibiting excellent cycling performance at high current densities.

[0047] Figure 5 The figures show the electrochemical impedance spectroscopy (EIS) spectra of the lithium-bismuth alloy anode prepared in Example 1 and the pure lithium metal anode prepared in Comparative Example 1. As can be seen from the figures, the lithium-bismuth alloy anode exhibits good interfacial compatibility, has a lower interfacial impedance compared to the pure lithium metal anode, and its lithium-ion transference number of 0.73 is significantly better than that of the lithium metal anode.

[0048] Figure 6 The figures show the electrochemical impedance spectroscopy (EIS) results and lithium-ion transference number of a symmetrical battery assembled with the lithium-bismuth alloy anode prepared in Example 1 and the pure lithium metal anode prepared in Comparative Example 1. As can be seen from the figures, the lithium-ion transference number of the pure lithium metal anode is only 0.31, significantly lower than that of the lithium-bismuth alloy anode.

[0049] Figure 7The graph shows the discharge capacity and coulombic efficiency of a full cell assembled from the lithium-bismuth alloy prepared in Example 1 and the pure lithium alloy prepared in Comparative Example 1, after long-term cycling tests at 1C rate. As can be seen from the graph, the full cell assembled from the lithium-bismuth alloy anode and the lithium iron phosphate cathode can stably cycle for more than 550 times at 1C rate, and its cycle life and capacity retention are significantly better than those of the pure lithium metal anode.

[0050] Figure 8 The graph shows the rate test results of a full cell assembled with the lithium bismuth alloy prepared in Example 1 and the pure lithium metal anode prepared in Comparative Example 1. As can be seen from the graph, the full cell assembled with the lithium bismuth alloy anode and the lithium iron phosphate cathode cycles stably at multiple rates from 0.1C to 5C, and its discharge capacity is higher than that of the full cell assembled with the pure lithium metal anode prepared in Comparative Example 1. Subsequently, it can cycle stably for more than 550 times at 1C, and its cycle life and coulombic efficiency are significantly better than those of the lithium metal anode.

[0051] Figure 9 This is a physical image of the lithium-bismuth alloy prepared in Example 1.

[0052] Figure 10 This is a physical image of the lithium-bismuth alloy prepared in Comparative Example 2.

[0053] Figure 11 This is a physical image of the lithium-bismuth alloy prepared in Comparative Example 3.

[0054] Figure 12 This is a physical image of the lithium-bismuth alloy prepared in Comparative Example 4. Detailed Implementation

[0055] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0056] In this invention, room temperature refers to 25±2℃.

[0057] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by those skilled in the art without creative effort are still within the scope of protection of the present invention.

[0058] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0059] Example 1

[0060] Take 0.452 mol of bismuth metal with a purity of 99 wt% and a particle size of 80 nm. Divide the bismuth metal into 3 parts: the first part contains 0.144 mol of bismuth metal, the second part contains 0.144 mol of bismuth metal, and the third part contains 0.164 mol of bismuth metal.

[0061] (1) In an argon glove box (water content and oxygen content are both less than 0.01ppm), 7.24mol of lithium metal ingot with a purity of 99wt% was placed in a double planetary stirrer. Starting from room temperature, the temperature was increased to 180℃ at a rate of 5℃ / min. The speed of the double planetary stirrer was controlled at 150 rpm and the temperature was maintained for 60 minutes to ensure that the lithium metal was completely melted and molten lithium was obtained.

[0062] (2) Under the condition of 220 rpm, the first part of bismuth metal was added to the molten lithium for 4 min, and the temperature was raised to 800℃ and stirred for 60 min. The mixture was then cooled to room temperature to obtain the first part of lithium-bismuth alloy.

[0063] (3) Under the condition of 240 rpm, the first lithium bismuth alloy was remelted (temperature was 180℃, holding time was 1h), the second part of bismuth metal was added to the melted first part of lithium bismuth alloy, the addition time was 3min, the temperature was raised to 900℃ and stirred for 120min, and then cooled to room temperature to obtain the second part of lithium bismuth alloy.

[0064] (4) Under the condition of 240 rpm, the second part of lithium bismuth alloy was remelted (temperature was 180℃, holding time was 1h), the third part of bismuth metal was added to the molten second part of lithium bismuth alloy, the addition time was 5min, the temperature was raised to 900℃ and stirred for 120min, and then cooled to room temperature to obtain lithium bismuth alloy.

[0065] (5) The lithium bismuth alloy is rolled thin by mechanical rolling (the rolling mill is set to 350 rpm and the temperature is 25°C). Specifically, it is rolled five times, and the thickness is reduced to 100 micrometers each time to obtain a large-area polycrystalline lithium bismuth alloy foil.

[0066] No overheating or sputtering occurred in this embodiment, and the yield of the lithium-bismuth alloy was 90%. See the product image below. Figure 9 .

[0067] Example 2

[0068] Take 0.52 mol of bismuth metal with a purity of 99 wt% and a particle size of 80 nm. Divide the bismuth metal into two parts: the first part contains 0.32 mol of bismuth metal and the second part contains 0.20 mol of bismuth metal.

[0069] (1) In an argon glove box (water content and oxygen content are both less than 0.01ppm), 7.24mol of lithium metal ingot with a purity of 99wt% was placed in a double planetary stirrer. Starting from room temperature, the temperature was increased to 200℃ at a rate of 8℃ / min. The speed of the double planetary stirrer was controlled at 120 rpm and the temperature was maintained for 45 minutes to ensure that the lithium metal was completely melted and molten lithium was obtained.

[0070] (2) Under the condition of 200 rpm, the first part of bismuth metal was added to the molten lithium for 3 min, and the temperature was raised to 700℃ and stirred for 120 min. The mixture was then cooled to room temperature to obtain the first part of lithium-bismuth alloy.

[0071] (3) Under the condition of 240 rpm, the first lithium bismuth alloy was remelted (temperature was 180℃, holding time was 1h), and the second bismuth metal was added to the melted first lithium bismuth alloy. The addition time was 4min, the temperature was raised to 1000℃ and stirred for 90min, and then cooled to room temperature to obtain lithium bismuth alloy.

[0072] (4) The lithium bismuth alloy is rolled thin by mechanical rolling (the rolling mill is set to 350 rpm and the temperature is 25°C). Specifically, it is rolled five times, and the thickness is reduced to 100 micrometers each time to obtain a large-area polycrystalline lithium bismuth alloy foil.

[0073] No overheating or sputtering occurred in this embodiment, and the yield of lithium-bismuth alloy was 70%.

[0074] Comparative Example 1

[0075] (1) In an argon glove box (water content and oxygen content are both less than 0.01ppm), 7.24mol of lithium metal ingot with a purity of 99wt% was placed in a double planetary stirrer. Starting from room temperature, the temperature was increased to 180℃ at a rate of 5℃ / min. The speed of the double planetary stirrer was controlled at 150 rpm and the temperature was maintained for 60 minutes to ensure that the lithium metal was completely melted and molten lithium was obtained.

[0076] (2) Cool the molten lithium to room temperature to obtain a lithium alloy;

[0077] (3) The lithium alloy is rolled thin by mechanical rolling (the rolling mill is set to 350 rpm and the temperature is 25°C). Specifically, it is rolled five times, and the thickness is reduced to 100 micrometers each time to obtain a large area lithium foil.

[0078] Comparative Example 2

[0079] Take 0.452 mol of bismuth metal with a purity of 99 wt% and a particle size of 80 nm. Divide the bismuth metal into two parts: the first part contains 0.42 mol of bismuth metal and the second part contains 0.032 mol of bismuth metal.

[0080] (1) In an argon glove box (water content and oxygen content are both less than 0.01ppm), 7.24mol of lithium metal ingot with a purity of 99wt% was placed in a double planetary stirrer. Starting from room temperature, the temperature was increased to 180℃ at a rate of 5℃ / min. The speed of the double planetary stirrer was controlled at 150 rpm and the temperature was maintained for 60 minutes to ensure that the lithium metal was completely melted and molten lithium was obtained.

[0081] (2) Under the condition of 220 rpm, the first part of bismuth metal was added to the molten lithium for 4 min, and the temperature was raised to 800℃ and stirred for 60 min. The mixture was then cooled to room temperature to obtain the first part of lithium-bismuth alloy.

[0082] (3) Under the condition of 240 rpm, the first part of lithium bismuth alloy was remelted (temperature was 180℃, time was 1h), and the second part of bismuth metal was added to the melted first part of lithium bismuth alloy. The addition time was 3min, the temperature was raised to 900℃ and stirred for 120min, and then cooled to room temperature to obtain lithium bismuth alloy.

[0083] (4) The lithium bismuth alloy is rolled thin by mechanical rolling (the rolling mill is set to 350 rpm and the temperature is 25°C). Specifically, it is rolled five times, and the thickness is reduced to 100 micrometers each time to obtain a large-area polycrystalline lithium bismuth alloy foil.

[0084] Sputtering and overheating occurred in step (2), and the yield of the lithium-bismuth alloy was 20%. See the product image below. Figure 10 .

[0085] Comparative Example 3

[0086] This comparative example is carried out using a method similar to that of Example 1, except that the temperature for heat preservation and stirring in step (2) is adjusted to 500°C and the time for heat preservation and stirring is 60 min.

[0087] Segregation occurred during the cooling process in this comparative example, resulting in an uneven lithium-bismuth alloy that failed to meet application requirements. See the product image below. Figure 11 .

[0088] Comparative Example 4

[0089] Take 0.452 mol of bismuth metal with a purity of 99 wt% and a particle size of 80 nm. Divide the bismuth metal into 3 parts: the first part contains 0.144 mol of bismuth metal, the second part contains 0.144 mol of bismuth metal, and the third part contains 0.164 mol of bismuth metal.

[0090] (1) In an argon glove box (water content and oxygen content are both less than 0.01ppm), 7.24mol of lithium metal ingot with a purity of 99wt% was placed in a double planetary stirrer. Starting from room temperature, the temperature was increased to 180℃ at a rate of 5℃ / min. The speed of the double planetary stirrer was controlled at 150 rpm and the temperature was maintained for 60 minutes to ensure that the lithium metal was completely melted and molten lithium was obtained.

[0091] (2) Under the condition of a rotation speed of 220 rpm, the first part of bismuth metal was added to the molten lithium for 4 min, and the temperature was raised to 800℃ and stirred for 60 min to obtain the first part of lithium-bismuth alloy molten liquid.

[0092] (3) Under the condition of a rotation speed of 240 rpm, the second part of bismuth metal was added to the first part of lithium bismuth alloy melt, the addition time was 3 min, the temperature was raised to 900℃ and stirred for 120 min to obtain the second part of lithium bismuth alloy melt.

[0093] (4) Under the condition of a rotation speed of 240 rpm, the third part of bismuth metal was added to the second part of lithium bismuth alloy melt for 5 min, the temperature was raised to 900℃ and stirred for 120 min, and then cooled to room temperature to obtain lithium bismuth alloy.

[0094] (5) The lithium bismuth alloy is rolled thin by mechanical rolling (the rolling mill is set to 350 rpm and the temperature is 25°C). Specifically, it is rolled five times, and the thickness is reduced to 100 micrometers each time to obtain a large-area polycrystalline lithium bismuth alloy foil.

[0095] In this comparative example, segregation occurred in the lithium-bismuth alloy preparation, resulting in decreased compositional uniformity. See the product image below. Figure 12 .

[0096] Test case

[0097] The polycrystalline lithium-bismuth alloy foil prepared in Example 1 and the large-area lithium foil prepared in Comparative Example 1 were respectively punched into circular pieces with a diameter of 16 mm and used as negative electrodes for assembling symmetrical cells and full cells.

[0098] Symmetrical cell testing: CR2016 coin cells were assembled in an argon atmosphere glove box (O2 and H2O content <0.5 ppm). Symmetrical coin cells (both sides are lithium-bismuth alloy foil or lithium metal foil) used a 1.0 M LiTFSI DME:DOL = 1:1 volume ratio solution (containing 2.0% LiNO3, LS009 type, Duoduo Chemical) as the electrolyte. To standardize the testing procedure, 75 μL of electrolyte was injected into each coin cell. A typical testing protocol was used: 5 mA cm⁻¹ -2 A current density of 5 mAh cm⁻¹ was achieved by performing stripping and deposition over 1 hour.-2 The areal capacity. The current density for lithium metal deposition / stripping is set to 5 mA cm⁻¹. -2 .

[0099] Electrochemical impedance spectroscopy measurements were performed at the Ivium electrochemical workstation in the Netherlands, with a frequency range of 0.1–100,000 Hz.

[0100] Full cell: 1M LiPF6 dissolved in EC:EMC:FEC = 3:7:1 (Vol%) was used as the electrolyte; Celgard 2500 was used as the separator; CR2016 was used for both positive and negative electrodes; the loading was 13 mg cm⁻¹. -2 The lithium iron phosphate electrodes are assembled into a full cell.

[0101] Electrochemical tests were performed on the assembled symmetric and full cells. Specifically, a 1.0 M LiPF6 solution with an EC:EMC:FEC ratio of 3:7:1 (LB515 type, Duoduo Chemical) was used as the electrolyte, and the test voltage range was 2.5–4.2 V. In the cycling test, the LFP full cell was first activated at 0.1 C for 3 weeks, and then at 1 C (1 C = 170 mA g). -1 Perform charge-discharge tests; or activate sequentially at 0.1 C, 0.5 C, 1 C, and 2 C for 5 weeks each, then perform charge-discharge tests at a 1 C rate. (1 C = 170 mA g) -1 )

[0102] See the specific results below. Figures 3-8 .

[0103] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for preparing a homogeneous lithium alloy, characterized in that: The method includes: (1) Melt lithium metal to obtain molten lithium; (2) Divide the metal M into N parts, where N≥2 and N is an integer; the molar amount of each part of the metal M is independently controlled within 5.5 mol% of the molar amount of lithium metal; the metal M is selected from at least one of bismuth, indium, silver, gold, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, tin, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, cadmium, antimony, hafnium, tantalum, tungsten, rhenium, iridium, platinum, mercury, thallium, lead, aluminum and polonium; (3) The first batch of M metal is mixed with the molten lithium for the first melt alloying, and then naturally cooled to obtain the first batch of lithium-M alloy; (3) After remelting the first lithium-M alloy, it is mixed with the second M metal for a second melt alloying and then cooled naturally to obtain the second lithium-M alloy; repeat this step until the N-1th lithium-M alloy is remelted and then melt alloyed with the Nth M metal for the Nth time, and then cooled naturally to obtain a homogeneous lithium alloy. The conditions for the first melting alloying, the second melting alloying, ... the Nth melting alloying are each independent: temperature of 600℃~1000℃, holding time of 1~4h; Based on the total molar amount of the M metal and the lithium metal, the total molar amount of the M metal is 5~30 mol.

2. The method for preparing a homogeneous lithium alloy according to claim 1, characterized in that: The metal M is selected from one of bismuth, indium, tin, zinc, aluminum, and silver; Preferably, the metal M is bismuth.

3. The method for preparing a homogeneous lithium alloy according to claim 1 or 2, characterized in that: The remelting temperature is 170℃~200℃, and the holding time is 30~90min.

4. The method for preparing a homogeneous lithium alloy according to claim 1 or 2, characterized in that: The conditions for melting lithium metal include: a melting temperature of 180~200℃, a stirring rate of 100~200 rpm, and a holding time of 30~60 min.

5. The method for preparing a homogeneous lithium alloy according to claim 4, characterized in that: The heating rate for the melting process is 5~10℃ / min.

6. The method for preparing a homogeneous lithium alloy according to claim 1 or 2, characterized in that: The first melting alloying, the second melting alloying, ... the Nth melting alloying were all carried out under stirring conditions, and the stirring rate was 200~250 rpm for each independently.

7. A method for preparing a homogeneous lithium alloy according to claim 1 or 2, characterized in that: Each molar amount of metal M independently accounts for 1.5 to 5.5 mol of the molar amount of elemental lithium metal.

8. A method for preparing a homogeneous lithium alloy according to claim 1 or 2, characterized in that: The lithium alloy preparation process is carried out entirely in an argon atmosphere, wherein the O content in the argon atmosphere is <10ppm and the H2O content is <10ppm.

9. The homogeneous lithium alloy prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the homogeneous lithium alloy of claim 9 as a lithium metal battery material.

Citation Information

Patent Citations

  • High-entropy lithium alloy negative electrode and preparation method thereof

    CN115986064A

  • Process for preparing lithium alloy negative electrode for solid-state battery by electrodeposition method

    CN119663387A